2003
DOI: 10.1095/biolreprod.103.016527
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Porcine Spermadhesins on the Susceptibility of Boar Spermatozoa to High Dilution1

Abstract: The effect of heparin-binding and non-heparin-binding spermadhesins on the viability, motility, and mitochondrial activity of boar spermatozoa at the high dilution (300,000 sperm/ml) to which sperm are exposed during the process of sex sorting by flow cytometry was investigated. Incubation of spermatozoa with heparin-binding spermadhesins caused a time- and dose-dependent decrease in the percentage of functional spermatozoa. The percentage of viable spermatozoa incubated at 38 degrees C with heparin-binding sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 39 publications
9
94
0
4
Order By: Relevance
“…33 Detection of AWN epitopes on boar spermatozoa bound in vivo to the ZP strongly suggests that the protein mediates sperm-ZP interaction. 34 While HBPs do not seem to promote sperm survival, at least in vitro, 35 the non-heparin-binding PSP-I and PSP-II, 36,37 which accounts for >50% of all SP proteins and forms a glycosylated heterodimer, 38 binds to the sperm surface and displays protective action on highly extended and processed spermatozoa. 39,40 The PSPs depict, moreover, clear immunostimulatory activities in vitro and in vivo, presumably in relation to specific cytokines.…”
Section: Proteomics Of the Ejaculatementioning
confidence: 99%
“…33 Detection of AWN epitopes on boar spermatozoa bound in vivo to the ZP strongly suggests that the protein mediates sperm-ZP interaction. 34 While HBPs do not seem to promote sperm survival, at least in vitro, 35 the non-heparin-binding PSP-I and PSP-II, 36,37 which accounts for >50% of all SP proteins and forms a glycosylated heterodimer, 38 binds to the sperm surface and displays protective action on highly extended and processed spermatozoa. 39,40 The PSPs depict, moreover, clear immunostimulatory activities in vitro and in vivo, presumably in relation to specific cytokines.…”
Section: Proteomics Of the Ejaculatementioning
confidence: 99%
“…Moreover, the heparin-binding BSP protein, pB1, has also been shown to stimulate capacitation of epididymal boar spermatozoa by inducing cholesterol and phospholipid efflux from the sperm membrane (Lusignan et al 2007), which has been extensively documented with bull BSP proteins. Incubation of highly diluted boar spermatozoa (extended to a level that mimicked sex-sorting: 0.3-1!10 6 sperm/ml) with heparin-binding proteins was detrimental to in vitro sperm function (Centurion et al 2003), causing a timeand dose-dependent decrease in the motility, viability and mitochondrial integrity of spermatozoa. Nonheparin-binding proteins showed the opposite effect ) and the protective effect was largely afforded by the PSP-I/PSP-II heterodimer.…”
Section: Stabilisation Of the Sperm Surface With Seminal Plasma Proteinsmentioning
confidence: 99%
“…The PSP-I/PSP-II heterodimer is present in all SP fractions, although its concentration increases gradually with a dose of the heparin-binding spermadhesins proteins and the total proteins in the post-sperm-rich fractions. Centurion et al (2003) demonstrated that sperm viability and motility are determined by the presence of the heparin-binding and non-heparin-binding spermadhesins in the incubation mixture. Thus, we can assume that differences between F1 and F2 regarding the sperm quality resulted from the presence of these specific proteins and their concentration in the analyzed portion of semen.…”
Section: Discussionmentioning
confidence: 99%